A classical case of the Gasul phenomenon. (28th October 2015) - Sabnis, Girish R.; Phadke, Milind S.; Kerkar, Prafulla G.
Abstract: This case demonstrates the development of secondary infundibular stenosis in a 10-year-old male child with documented large non-restrictive perimembranous ventricular septal defect in infancy – the classical Gasul phenomenon.